Estrategias que generan mayor competitividad del aceite de palma para exportar de Colombia a España (2020)
This document compiles literature on the palm sector in Colombia, recognizing how it can have an effect on the country ́s economy through a review of documentation on oil productivity over time and the formulation of strategies to generate greater competitiveness. The production and export of palm oil in Colombia is identified knowing the importance of the sector in Colombian agribusiness, in this case of research the preferences and demand for oil within the country to which you want to export, Spain, and the importance of this as raw material for the production of renewable energies that today are replacing fossil fuels. Finally, strategies are proposed to increase competitiveness, identifying the Colombian institutions that support the production and export of palm oil. In which we identify that a new perspective in technological investment and innovation of the production process is necessary for a subsequent export.